Ekstraksi Daun Kelor (Moringa Oliefera) dengan Metode Maserasi, Ultrasonik, dan Sokletasi: Perbandingan Hasil dan Efisiensi - Izzati, Aluna Monalaika; Margareth, Angelica; Mahardika, Aurellia Azzahra; Dewi, Dea Puspa; Salsabila, Keisya Yumna; Ayudya, Malika Aziza; Karima, Naura Putri; Rahmadani, Sinta; Mufaza, Wahya; Herayati; Syaputra, Iwan Syahjoko (PT. Pubsains Nur Cendekia, 2025)
This research aims to optimize the extraction method for natural compounds from the Moringa oleifera plant in order to obtain the most effective method for isolating bioactive compounds that have the potential to be applied in natural cosmetic products. Four extraction techniques were compared in this study, namely ultrasonic extraction, maceration, digestion, and soxhletation, using methanol, n-hexane, and water as solvents. The highest yield was obtained from the ultrasonic assisted extraction (UAE) method with a concentration of 2.4% (w/v) this method is carried out for 60 minutes using a frequency of 60 kHz, followed by soxhletation at 0.8% (w/v). Phytochemical tests showed the presence of flavonoids, tannins, alkaloids and terpenoids, while saponins were not detected in several solvent systems due to differences in polarity. These results show that the UAE method is the most efficient technique for isolating active compounds from Moringa leaves, so it has the potential to be used in the formulation of natural cosmetic preparations, especially as an antioxidant in skin care.